Description and characteristics of chert nodules in Appollonia Formation, Al Hmmeda road-cut, Al Jabal Al Akhdar, NE Libya - Elfigih, Omar; El Degheeli, AL- Moatasem Bellah (Libyan Journal of Science &Technology, 2022)
Physical, petrographic and bulk elements analysis of Chert Nodules in Appollonia Formation, Al Hmmeda road-cut were conducted and showed that the origin of these chert by replacement. The suspected siliceous organic matters are of low crystallized silica and were dissolved under the influence of increasing temperature and pH. Most of the chert was localized in the limestone and dolomitic limestone of Appollonia Formation (nodular zone) by percolation of silica-rich solution along microfractures and porous/permeability zones. This local porosity and permeability variations, mostly produced mixing of the diffused digenetic fluids. This process produces the nodular form of the cherts in the Appollonia mudstone facies in the nodular zone, while less marked permeability variations could have produced more regular tabular bodies of chert, which were not observed at least in the studied section. The absence of chert nodules in some adjacent rocks and even at higher elevation in the Appollonia stratigraphic section (nonnodular zone), might reflect effective exhaustion of the silica supply, fewer microfractures condition and perhaps dilution by the marine water of highly reduced silica-rich solution.